The Age of Light, Soap, and Water : Moral Reform in English Canada, 1885-1925 - Valverde, Mariana, 1955- (Book collections on Project MUSE., 2008)
"BACK IN PRINT WITH A NEW INTRODUCTION The turn of the last century saw a great wave of moral fervour among Protestant social reformers in English Canada. Their targets for moral reform were various: sex hygiene, immigration policy, slum clearance, prostitution, and "white slavery."Mariana Valverde's groundbreaking The Age of Light, Soap, and Waterexamines the work and the ideas of moralist clergy, social workers, politicians, and bureaucrats who sought to maintain - or create - a white Protestant Canada. The morality idealized by evangelical, feminist, and medical activists was not, as is often assumed, completely repressive and puritanical. On the contrary, the self-defined social purity movement at the centre of this book talked endlessly about sex in order to create a healthy sexuality among both native-born and immigrant Canadians. Sexual health was linked to racial purity, and both of these were in turn linked to efforts to abolish urban slums by means of symbolic as well as physical "light, soap, and water."This study uncovers a little known dimension of Canadian social history and shows that moral reform was not the project of a marginal puritanical group but was central to the race, class, and gender organization of modern English Canada.